The effects of the Gawad Kalinga Resettlement program to the general self-efficacy, task orientation and functional social contacts of the schooled adolescents in Gawad Kalinga Villages in Iloilo City. - Caminos, Ann Marie P.
There have been a lot of studeis conducted about the gawad Kalinga (GK) adult rresidents. This descriptive study will venture on the schooled adolescents (13-19 yrs. old) in the two (2) GK sites, the Sooc, mandurriao Village and the Buntatala, Jaro Village, specifically about their General Self-Efficacy(GSE), Task-orientation and Functional Social Contacts (FSC). Genral Self-Efficacy Test by Schwarzer (2009) and FGD quationnaires are the amterials used in this study. There were 47 schooled adolescents. Each GK was divided into 2 groups (highest and lowest GSE) with 5 participants for each FGD session. It is found that GK program helped the respondents in terms of their adaptation in thier new environment. However, the program does not affect their task-orientation because it is mainly influenced by their families. The program does not also serve as a direct functional social contact because of the type of social network they seek in times of problem.